Developing Best Measurement and Reporting of Waqf Institutions: Socio-Economics and Governance Impact (Indonesia Case) - Aryani, Dwi Nita; B, Bunyamin; Mauludin, Hanif; Masruki, Rosnia; Hanefah, Mustafa Mohd (LPPM IAIN Kudus, 2021)
This study aims to analyse the current practices of disclosure of financial and non-financial reports of waqf institutions in Indonesia; to identify the performance indicators concerning social economic and governance impact of waqf; to suggest the best reporting framework for waqf institutions in Indonesia. A qualitative method was employed to measure the content analysis of annual report. Data are collected by downloading annual reports of waqf institutions from their website. Twenty waqf boards of 201 registered waqf institutions as the sample of participants. The disclosure of performance reports were measured by counting 57 disclosure items. The results indicate that waqf boards in Indonesia do not have a guidance or list for reporting their activities; methods on how to assess waqf board performance and the impact of waqf on social-economic and governance. They did not comply with 57 disclosure items, and none of waqf board reported the impact of waqf on social-economic and less governance. The proposed guidance and measurement will give managerial implications and useful for waqf boards to make good reports, and assess the impact of waqf on social, economic, and improving its governance.